INVESTIGATING THE RELATIONSHIP BETWEEN MONETARY POLICY UNCERATAINTY INDEX OF US AND THE DOLLAR INDEX - Samet GÜRSOY; Kumar PRADHAN; Sandhyarani ROUT; Mesut DOĞAN (Bina Nusantara University, 2022)
In this paper, we investigate the effect of the monetary policy uncertainty index for the US on the dollar index. In other words, in this study, the relationship between the US MPU (USM) and the Dollar index (XD) was examined. We employ the Hatemi-J (2012) asymmetric causality test from the period January 1986 through August 2020 by using monthly data. The results of the empirical analysis prove a strong non-linear causal relationship between the variable MPU index and XD. The overall result ascertains a positive and negative bidirectional asymmetric and non-linear causality existing between the variables XD and USM index. The results of the empirical investigation endorse important policy inputs for the macroeconomic policy formulators.